Cloud Management Platform Selection: A Case Study in a University Setting - Cocozza Garro, Francisco José (2015)
Cloud Computing has gained importance in recent years. There are many implementations' analyses and evaluations of Cloud Management Platforms (CMPs) in the literature. Moreover, the context and characteristics differ drastically between implementations, depending on the user requirements and usage context. This paper presents a case study of the process we followed to select a Cloud Computing management platform to be deployed in a University. Administrative and academic requirements were gathered and studied to define the most appropriate platforms. We present an overview of available CMPs. Moreover, we show a set of comparison criteria that could be used to determine which CMP adapts best to the cloud deployment scenario.